1384. RSV Monoclonal Antibody (MK-1654) Phase 1 Pharmacokinetics (PK) in Healthy Adults and Population PK Modeling to Support Pediatric Development. (26th November 2018) - Maas, Brian; Aliprantis, Antonios; Wolford, Dennis; Fayad, Ghassan; Vora, Kalpit; Geng, Dong; Ma, Hua; Caro, Luzelena
Abstract: Background: Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infection and hospitalization in infants. MK-1654 is a monoclonal antibody (mAb) being developed to prevent RSV infection in infants and is undergoing evaluation in a Phase 1 study. Incorporation of YTE mutations extend its half-life to allow for dosing once every RSV season. Preliminary Phase 1 PK results and the development of a population PK model that characterizes adult PK to predict pediatric exposures are presented here. Methods: In this double-blinded Phase 1 study, 152 healthy males and females of nonchildbearing potential aged 19–59 years were randomized in a 3:1 ratio to receive a single dose of MK-1654 or placebo as a bolus intramuscular injection (IM) or in an intravenous infusion (IV) over 2.5 hours. Dose levels included 100 mg IM, 300 mg IM, 300 mg IV, 1, 000 mg IV and 3, 000 mg IV. Serial serum samples were collected to measure MK-1654 PK via a validated LC/MS assay. A noncompartmental PK analysis was conducted using preliminary data from 60 subjects up to Day 150 (900 observations). A population PK model was developed to simultaneously characterize the IM and IV adult PK data and to predict pediatric PK through allometric scaling. Pediatric MK-1654 PK was predicted for several IM doses for a typical sized infant (35 weeks gestational age at birth; 4 months chronological age at dosing; 50th percentile weight). Results: In adults, the median time to maximum concentration observed was 6–10 days following IM injection. The apparent half-life of MK-1654 ranged from 70–85 days after either IM or IV doses. The estimated IM bioavailability was 71%. Cmax and AUC0-90 days increased dose proportionally following IV administration. MK-1654 adult PK was best characterized using a two-compartment model with first-order elimination. IM absorption was described using a first-order rate constant with lag time. Inter-individual variability was included for clearance (CL and Q), central volume (V2), and absorption rate (Ka). The pediatric model suggested apparent terminal half-life in a typical infant is shorter than adults, likely being driven by infant growth during treatment. Conclusion: Predicted infant PK profiles support further development of MK-1654 in children. Disclosures: B. Maas, Merck: Employee and Shareholder, Salary and stock options. A. Aliprantis, Merck: Employee and Shareholder, Salary and stock options. D. Wolford, Merck: Employee and Shareholder, Salary and stock options. G. Fayad, Merck: Employee and Shareholder, Salary and stock options. K. Vora, Merck: Employee, Salary. D. Geng, Merck: Employee and Shareholder, Salary and stock options. H. Ma, Merck: Employee and Shareholder, Salary and stock options. L. Caro, Merck: Employee and Shareholder, Salary and stock options.